Local Wisdom-Led Business Communication: A Case Study of “Barosok” in Livestock Market in West Sumatera Indonesia - Evanita, Susi; Andriani, Chichi; Asri, Zul; Trinanda, Okki; Fahmi, Zul (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2024)
Business communication with local wisdom of ethnic Minangkabau in addition to aiming for business interests but still prioritizing social and human values. This research aims to reveal the non-verbal symbols used in the